A deep learning-based model for detecting depression in senior population - Lin, Yunhan; Liyanage, Biman Najika; Sun, Yutao; Lu, Tianlan; Zhu, Zhengwen; Liao, Yundan; Wang, Qiushi; Shi, Chuan; Yue, Weihua (Frontiers in Psychiatry, 2022)
Objectives: With the attention paid to the early diagnosis of depression, this study tries to use the biological information of speech, combined with deep learning to build a rapid binary-classification model of depression in the elderly who use Mandarin and test its effectiveness. Methods: Demographic information and acoustic data of 56 Mandarin-speaking older adults with major depressive disorder (MDD), diagnosed with the Mini-International Neuropsychiatric Interview (MINI) and the fifth edition of Diagnostic and Statistical Manual of Mental Disorders (DSM-5), and 47 controls was collected. Acoustic data were recorded using different smart phones and analyzed by deep learning modelwhich is developed and tested on independent validation set. The accuracy of the model is shown by the ROC curve. Results: The quality of the collected speech affected the accuracy of the model. The initial sensitivity and specificity of the model were respectively 82.14% (95%CI, [70.16% to 90.00%]) and 80.85% (95%CI, [67.64% to 89.58%]). Conclusion: This study provides a new method for rapid identification and diagnosis of depression utilizing deep learning technology. Vocal biomarkers extracted from raw speech signals have high potential for the early diagnosis of depression in older adults.